Relationship between Self-Directed Learning and Self-Regulated Learning in Problem-Based Learning: Problem-Based Learning - Nisa, Waqar Un; Aman, Khaliq; Murtaza, Sana; Abdullah, Zainab; Gul, Naveed (Pakistan Journal of Health Sciences, 2024)
Self-Directed Learning (SDL) was crucial for developing Self-Regulated Learning (SRL) skills, essential for success in Problem-Based Learning (PBL) settings. Objective: To explore the association between SDL and SRL, focusing on motivation, self-efficacy, and cognitive strategies. Methods: A longitudinal study design was conducted with 250 medical students in the PBL curriculum at Rawal Institute of Health Sciences Islamabad. Stratified random sampling ensured representation across academic performance levels. A structured survey assessed SDL (goal-setting, time management, and self-assessment) and SRL (motivation, self-efficacy, cognitive strategies, and behavioural regulation) using a 5-point Likert scale. Data were analysed using Chi-Square Goodness-of-Fit tests to explore distribution patterns, Bivariate Pearson correlation for relationships between SDL and SRL, and One-Way ANOVA to identify SRL differences across performance levels, with a significance threshold set at p < 0.05. Results: Significant engagement in SDL components, goal-setting and intrinsic motivation (p = 0.001), with moderate correlations between specific SDL skills and SRL outcomes. Time management showed a weak but significant correlation with cognitive strategies (p = 0.03), suggesting an impact on SRL behaviours. No significant differences were observed in SRL skills across academic performance levels (p > 0.05), indicating a uniform development of self-regulation skills regardless of prior achievement. High engagement in PBL discussions and peer collaboration further underlines these activities as central to fostering SDL and SRL. Conclusion: SDL in PBL shows a positive, however modest, impact on SRL outcome, management and self-assessment, which could further enhance SRL in medical education settings.